Study of the Effect of Damping Pendulum Motion on the Efficiency and Stability of the New Holland TC54 Combine Harvester Under Different Operating Conditions - Mohsin, Yahya y; Mahmood, Farooq Dawas; Maher, Jarullah (jurnal makanan tropis dan teknologi agroindustri, 2026)
This study investigates the effect of slope angle and forward operating speed on the optimal performance of the harvesting process of a combine equipped with a decelerating pendulum device that mechanically and hydraulically changes the angle of inclination of the combine. Three harvesting slope angles (0-5°, 10-15° and 20-25°) and three forward speeds (3, 5 and 7 km/h) were tested using a New Holland TC54 harvester, The experiment was carried out using a randomised complete block design (RCBD) with (27) experimental units distributed in three replications. Several key performance indicators were measured including:Fuel consumption (litres/hour), operational efficiency (%), harvester stability and total grain loss as a percentage. The results showed that soils with steeper slopes significantly increased fuel consumption and grain loss, while reducing machine stability. The best performance was achieved at a slope angle of (10-15°) and a speed of (5) km/h, with a field capacity of (5.60) tons/hour, fuel consumption of 24.10 liters/hour, and the lowest grain loss of (2.3%), The effects of slope and speed were found to be statistically significant (P < 0.05), reflecting the importance of improved combinations in significantly enhancing operational efficiency, reducing harvest losses, and thus improving the overall performance of the agricultural system .